Experiences of place attachment and mental wellbeing in the context of urban regeneration. (July 2021) - Lomas, Michael J.; Ayodeji, Eunice; Brown, Philip
Abstract: Urban regeneration is an important policy focus across the European Union, with initiatives seeking to address inequalities in public health. Although theoretically such initiatives should produce benefits for mental wellbeing, this lacks strong supporting evidence. The current research addressed a prior overreliance on quantitative methods and underappreciation of the psychological significance of place, through the adoption of qualitative interviews with residents, as part of an independent review of a £650m regeneration project. Interpretative phenomenological analysis was utilised to explore the processes involved in residents' mental wellbeing and place attachment. Analysis developed three super-ordinate themes: 'feelings of control', 'social and community relations', and 'understandings and definitions of place'. These highlight issues relating to physical health, social isolation, community cohesion, as well as the potential for regeneration activities to undermine various elements of the people-place relationship. Highlights: Delivery leading to reduced feelings of autonomy and control. Refurbishment work contributing to physical health concerns with accomodating measures inadequate. Removal of social spaces and resident relocation leading to increased isolation. Changing population demographics implicated alongside issues of community cohesion. Potential for regeneration to undermine various elements of place attachment.